PENGARUH KEBUTUHAN MEMILIKI NPWP, KEMUDAHAN DALAM PERPAJAKAN, DAN PEMAHAMAN WAJIB PAJAK TERHADAP KEPEMILIKAN NOMOR POKOK WAJIB PAJAK (NPWP) (Studi Empiris Pada Pengusaha UMKM di Kota Pekanbaru) - Lega Bestari; Yessi Mutia Basri; Rheny Afriana Hanif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the effect caused by the need to have a TIN , convenience in taxation , taxpayers understanding to the ownership TIN. This study used a simple technique accidental sampling with a sample of 100 people who have been determined based on those results slovin formula . Data collection techniques in this study is a questionnaire , the data is processed using Logistic Regression with SPSS version 20 .The results of the testing that has been done , that factor does not affect the need to have a TIN to ownership variables NPWP . While the convenience in taxation factor and tax payers understanding factors affect the ownership TIN variables.Keywords : Needs to have a TIN , convenience in taxation , and understanding taxpayars, ownership taxpayer identification number (TIN)